ACCURACY OF INTRAOPERATIVE RADIONUCLIDE SCINTIGRAPHY FOR DETECTION OF SENTINEL LYMPH NODE USING 99MTC LABELED NANOCOLLOIDS IN EARLY BREAST CARCINOMA: Intraoperative Radionuclide Scintigraphy - Dar, Zaigham Salim; Aziz, Omer bin Abdul; Sajid, Tanveer; Ali, Mujahid Khalid (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the accuracy of intraoperative radionuclide scintigraphy for detection of sentinel lymphnode (SLN), using 99mTc-Nanocolloids, in patients with early breast carcinoma.Study Design: Cross sectional analytical study.Place and Duration of Study: Nuclear Medical Centre, Armed Forces Institute of Pathology, Rawalpindi anddepartment of Surgery, Pak Emirates Military Hospital, Rawalpindi, from Jul 2012 to Jun 2013.Patients and Methods: After fulfilling the inclusion and exclusion criteria and taking written informed consent,67 patients of carcinoma breast were enrolled in the study. Each patient was injected with 37 MBq of 99mTc-Nanocolloids, via sub areolar, peri-tumoural route, pre-operatively. SLNs were identified using handheld gammaprobe followed by excision biopsy. Patients, then, underwent modified radical mastectomy with dissection ofaxillary lymph nodes (ALN) and the samples were sent for histopathology.Results: Out of 67 patients, 28 to 77 years of age (mean ± SD of 49.61 ± 11.572 years), 17.9% (12) patients hadT1tumour while 82.1% (55) had T2 tumour (mean ± SD of 3.48 cm ± 1.050 cm). Histopathology revealed nometastasis in SLNs as well as ALN of 55.2% (37) patients while 40.3% (27) patients were positive for both.However, in 4.5% (3) patients SLNs were negative for metastasis with positive ALN. Diagnostic accuracy wascalculated to be 95.5%, sensitivity 90%, false negative rate 4.5% and negative predictive value 92.5%.Conclusion: Intraoperative radionuclide scintigraphy, using 99mTc-Nanocolloids and handheld gamma probe isa reasonably accurate technique for localization of SLNs in early breast carcinoma.